Prevalence of periodontitis and its impact on quality of life among subjects with rheumatoid arthritis / Philip Han Sheng Hui - Philip Han, Sheng Hui (2019)
Background and Objective(s): Traditional clinical measurement parameters alone cannot capture the extent of disease. Quality of life (QoL) measures provide understanding from the patient’s perspective. There is a gap in the knowledge of the impact of periodontitis (PD) on QoL among rheumatoid arthritis (RA) subjects. This study aimed to determine the prevalence of PD in Malaysian RA patients and assess the impact on their health related QoL (HRQoL) and oral health related QoL (OHRQoL). Materials and Methods: Subjects from periodontology and RA clinics were screened. Complete periodontal examination was then performed. Subjects were divided into 4 groups: RA(+)PD(+), RA(+)PD(-), RA(-)PD(+) and RA(-)PD(-). Questionnaire on sample characteristics and Malaysian versions of Oral Health Impact Profile (OHIP14(M)) and Health Assessment Questionnaire (HAQ-DI)) were answered. Results: Fifty percent of 108 screened RA subjects recorded BPE scores ‘3’ or ‘4’. Prevalence of PD in 87 RA subjects who consented for periodontal examination was 33.3% (4.6% mild, 10.3% moderate, 18.4% severe PD). OHIP-14(M) severity score was highest in the RA(-)PD(+) group (17.23±10.36) but only significantly higher than RA(-)PD(-) group (p < 0.05). HAQ-DI scores of RA(+)PD(-) and RA(+)PD(+) groups were significantly higher (p<0.05) than the non-RA groups. Differences remained significant when age, gender, education level and brushing frequency were controlled. There was a weak negative correlation (r = -0.269, p<0.05) between the number of teeth and OHRQoL in the RA(+)PD(-) group but none from other periodontal parameters. Conclusion: The prevalence of PD in RA subjects in this study was lower than that reported worldwide. Subjects with PD have significantly lower OHRQoL than subjects iv without PD. Subjects with RA have significantly lower HRQoL compared to their healthy counterparts regardless of PD status. Keywords: periodontitis, rheumatoid arthritis, quality of life